Tenascin-C fragments are endogenous inducers of cartilage matrix degradation. - Sofat, N; Robertson, S; Hermansson, M; Jones, J; Mitchell, P; Wait, R (2012)
Cartilage destruction is a hallmark of osteoarthritis (OA) and is characterized by increased protease activity resulting in the degradation of critical extracellular matrix (ECM) proteins essential for maintaining cartilage integrity. Tenascin-C (TN-C) is an ECM glycoprotein, and its expression is upregulated in OA cartilage. We aimed to investigate the presence of TN-C fragments in arthritic cartilage and establish whether they promote cartilage degradation. Expression of TN-C and its fragments was evaluated in cartilage from subjects undergoing joint replacement surgery for OA and RA compared with normal subjects by western blotting. The localization of TN-C in arthritic cartilage was also established by immunohistochemistry. Recombinant TN-C fragments were then tested to evaluate which regions of TN-C are responsible for cartilage-degrading activity in an ex vivo cartilage explant assay measuring glycosaminoglycan (GAG) release, aggrecanase and matrix metalloproteinase (MMP) activity. We found that specific TN-C fragments are highly upregulated in arthritic cartilage. Recombinant TN-C fragments containing the same regions as those identified from OA cartilage mediate cartilage degradation by the induction of aggrecanase activity. TN-C fragments mapping to the EGF-L and FN type III domains 3-8 of TN-C had the highest levels of aggrecan-degrading ability that was not observed either with full-length TN-C or with other domains of TN-C. TN-C fragments represent a novel mechanism for cartilage degradation in arthritis and may present new therapeutic targets for the inhibition of cartilage degradation.